Líneas base, dosis diagnóstico y medición periódica de resistencia a imidacloprid, spinosad y carbosulfan en poblaciones de adultos de Thrips palmi (Thysanoptera: Thripidae en el Valle del Cauca, Colombia - Rodríguez Torres, Isaura Viviana; Durán Sanchez, I.C.; Morales, H; Cardona Mejía, César (2003)
The melon thrips (Thrips palmi) have become a very significant pest of snap beans, beans, eggplants and cucumbers, and other crops, since they were first reported in Colombia. The response of farmers to this problem has been the excessive pesticide use. With the aim of monitoring changes on the susceptibility of thrips populations to certain insecticides that are still effective, the line base data, LC50and LC90 values and diagnostic doses for imidacloprid, spinosad and carbosulfan were established. We used an adult population of a susceptible strain of T. palmi maintained at CIAT since 1997. Imidacloprid was evaluated as a systemic pesticide by immersing leaves with petioles in insecticide solutions. Disks of foliage treated in this fashion were placed on agar in petri dishes. Spinosad and carbosulfan were evaluated as contact pesticides using the foliage dipping technique. Disks of the treated foliage were placed on petri dishes with agar. The diagnostic doses were 1.000 ppm (imidacloprid), 2.000 ppm (spinosad) and 2.000 ppm (carbosulfan). These doses were used for field monitoring of resistance in five zones of the Cauca Valley where heavy use of pesticides for the control of T. palmi occurs. No evidence of resistance to any of the evaluated pesticides was found. Nevertheless, we recommended the performance of periodic monitoring in order to detect changes in resistance of the thrips over time.